Detection and Pathogenicity Features of Pseudomonas Aeruginosa in Patients with Skin Infection - Alkheeqani, Buthaina; Khassaf, Ahmed (University of Thi-Qar Journal of Science, 2024)
Pseudomonas aeruginosa is a Gram-negative opportunistic pathogen often concerning studies in bacterial resistance and pathogenicity. Nosocomial infections from burns and surgical site infections are often caused by destruction of the  natural defenses of the skin, exposed matrix proteins and inflammatory factors being compromised making it easier for P. aeruginosa to colonize the area leading to infection. For this experiment, 113 wound and burn samples collected from hospitalized immunocompromised patients. 26 isolates tested positive for P. aeruginosa with associated virulence factors. Identification of bacteria   concluded   biochemical assays, antibiotics susceptibility, and the ability of biofilm formation and the presence of P.aeruginosa in different skin samples. The study showed 66.53% of the isolates were resistant to antibiotics including (AK, GN, IPM, LEV, CIP, ATM, PRL and TZP), while prevalence of sensitivity was to Meropenem (65.38%) and Cefepime (19.23%).Biofilm formation assay showed all P.aeruginosa isolates formed biofilms at different levels (65.3%) weak (27%) moderate and (7.7%) strong biofilm formation. Following the study's conclusion, consider specific strategies for managing and shielding future generations against P.aeruginosa bacterial infections.